La lúdica como estrategia de entrenamiento en la motivación de jugadores de voleibol infantil. - Daquilema Jara, José Andrés (2024)
The current research aimed to implement playful games as a training strategy to increase the motivation of children's volleyball players category; therefore, this research used a mixed methodological approach at the descriptive level. It was necessary to apply the SMS Test of Sports Motivation through surveys to children in the sixth year of primary education at the La Salle Educational Unit. The purpose was to analyze the level of motivation before and after the intervention, correlating the results of the pretest and posttest. The findings revealed that the strategies implemented significantly improved children's perception and decision to practice sports. In conclusion, properly motivating students is crucial to encouraging their commitment and enjoyment of sport. The study underlines the importance of play methods in the integral development of young volleyball players. The European Commission has recently launched a survey of the impact of the EU's energy-saving policies on the environment.